The Effect of Independent Learning and Learning Discipline on Student Learning Outcomes in Economics Subject Ips of 10th Grade During Covid-19 Pandemic in High School Negeri 8 Medan Academic Year 2021/2022 - Siagian, Novayanti; Sianipar, Vina Merina Br (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to determine the effect of independent learning and disciplined learning on student learning outcomes in economics class X social studies during the covid-19 pandemic at SMA Negeri 8 Medan for the academic year 2021/2022. This type of research is a type ofresearch  survey with a quantitative approach. The population in this study were all students of class X IPS SMA Negeri 8 Medan for the academic year 2021/2022 with a total of 128 students while the number of samples was 32 students. The analytical method used in this study is the normality test, multicollinearity test, regression test, partial hypothesis test (t test), simultaneous hypothesis test (test F) test the coefficient of determination (R2).The results showed that independent learning and learning discipline had a positive and significant effect on student learning outcomes with the equation Y = 44.5911 + 0.244X+ 0.344 X2 and a partial hypothesis test (t test) for the variable X1 obtained the value of tcount > ttabe.l (3.553 > 2.032) and the significant value of independent learning is 0.00 < 0.05 which means that there is a positive and significant effect between independent learning on learning outcomes. Furthermore, for the variable X2 , the value of tarithmetic > ttablel (4.548 > 2.032) and the significant value of learning discipline on student learning outcomes of 0.001 < 0.05 stated that there was a positive and significant effect between independent learning on student learning outcomes.